The Relevance of Warahan Teaching Material in Developing Character Education Value for the Language Class - Siti Fitriati; Nuruddin Nuruddin; Eva Leiliyanti (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the relevance and feasibility of Warahan's teaching materials in developing character education values for language classes. This study used a qualitative approach with content analysis methods. The data was taken from the warahan literature, still developing in the Jabung Lampung community, with as many as seven warahan stories. Data were collected through observation and interviews with seven community leaders, traditional leaders, and ten language teachers at secondary schools in Jabung regarding their understanding of warahan oral literature. Data analysis techniques included (1) problem formulation, (2) selection or categorization of data sources, (3) elaboration of data categories based on operational definitions, (4) reliability checking, (5) data analysis, research, reports, and evaluation of research results. From the results of data analysis, it is concluded that written and oral literature is appropriate for use as teaching material in language classes and is relevant to current conditions in developing character education values that the government has set. Of the seven warahan stories analyzed, three main values were found in character education: religious, social, and humanist values (humanity). Of the three main character education values, 17 were found, including religious, sacrifice, polytheistic, mutual respect, trust, patience, lack of sympathy, courage, unyielding, and careless values. Value of Pride, Value of Caring, Value of Not Caring, Value of Cooperation, Value of Honesty, Value of Responsibility, and Value of Innovation and Creativity.